Unions, Two-Tier Bargaining and Physical Capital Investment: Theory and Firm-Level Evidence from Italy - Gabriele Cardullo; Maurizio Conti; Giovanni Sulis (Institute of Labor Economics (IZA), 2018)
In this paper we present a search and matching model in which firms invest in sunk capital equipment. By comparing two wage setting scenarios, we show that a two-tier bargaining scheme, where a fraction of the salary is negotiated at firm level, raises the amount of investment per worker in the economy compared to a one-tier bargaining scheme, in which earnings are entirely negotiated at sectoral level. The model's main result is consistent with the positive correlation between investment per worker and the presence of a two-tier bargaining agreement that we find in a representative sample of Italian firms.
Keywords: J51; J64; E22; 330; unions; investment; hold-up; two-tier bargaining; control function